AUGMENTED REALITY-BASED LEARNING MEDIA TO IMPROVE MATHEMATICAL PROBLEM-SOLVING ABILITY IN ELEMENTARY SCHOOLS - Hariyono, Mohamad; Purwanti, Kartika Yuni; Munfariqoh, Aqidatul; Muryaningsih, Sri; Mustadi, Ali (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
The importance of mathematics in everyday life is the reason students are expected to understand and be able to apply the mathematics learning they have received at school. One of the abilities in mathematics is problem-solving ability. Abstract mathematics requires concrete learning media so that it is more acceptable to students in elementary schools during learning. The media that is currently frequently used is IT-based learning media. One is augmented reality, which integrates two-dimensional media into three dimensions. This research tests whether increased reality-based learning media can improve problem-solving abilities. The data analysis used is the normality test, paired sample t-test, and normalized gain test. The research results show that augmented reality-based learning media can improve students' problem-solving abilities